FURTHER NOTES ON THE FERN-GENUS HETEROGONIUM PRESL - HOLTTUM, R. E. (REINWARDTIA, 1950)
In the "Sarawak Museum Journal," volume V (1949), pages 156-166,I gave a revised account of the genus Heterogonium Presl, based on specimens in the Singapore herbarium.Dr M. A.Donk wrote subsequently pointing out that specimens at Bogor (Buitenzorg) add materially to the information contained in that paper.The present paper gives the result of a study of the Bogor specimens.I am glad to express my gratitude to Dr Donk for calling my attention to species which I had overlooked when searching literature on Malaysian ferns for indications of affinity to Heterogonium. The Bogor material includes the type specimens of Acrostichum teysmannianum Bak.,Phegopteris schizoloma v. A. v. R. Dryopteris sagenoides forma contracta v. A. v. R.,Polybotrya nieuwenhuisii Racib.and Polybotrya nieuwenhuisii var. brooksii v. A. v. R.,also many sheets of H. giganteum, and material of H.sagenoides from a wider geographic range than I had previously seen.Summarizing the results of the present paper,I have united H.nieuwenhuisii and H. stenosemioides of my former paper,and have also united H.saxicola with H. giganteum.Further, I now recognize a second exindusiate species allied to H.sagenoides; but the variation in pubescence among exindusiate specimens, as within the species H.sagenoides proper,is very considerable,and I find it very difficult to draw specific limits. It is likely that there are local races, but much more field work in many localities is necessary before one can speak with certainty about this or define their status taxonomically. One interesting fact is that no exindusiate specimens of this alliance have been found in the Malay Peninsula, whereas Peninsular collections of indusiate H. sagenoides are more abundant than from any other area.It is especially the variation in pubescence among specimens of H.sagenoides,and the lack of clear-cut varieties or subspecies within the Malay Peninsula, that deters me from distinguishing more species outside the Peninsula, based on few specimens.Another generalization based on many specimens is that fertile fronds are always much less hairy on the lower surface than sterile fronds of the same plant.As regards another kind of character, namely venation,I have noted that fronds of immature plants may not show the low